Effect of CO2 sequestration on soil liquefaction in geological pits - T. Laxmi; H. M. Padhy; Pranati Mishra; Rohit Singh (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper deals with review of the previous related research on evaluation of soil liquefaction due to Carbon sequestration by various Carbon Capture Sequestration processes in geological pits. It provides critical literature recommendations on evaluation of soil liqu efaction potential assessment. The detection of soil liquefaction by using seismic records has been developed by various researchers. With this information, the evaluation of soil liquefaction are well under stood and this lead to a more precise and confident output. Gaining support for CCS will require engaging the interest and building the support of a variety of stakeholders, each with differ ent perspectives and goals. Although, CCS builds upon a technology base developed over more than half a century by the oil and gas industry. In the past, the industrially released CO 2 had been introduced to ocean which was harming the aquatic animals. In view of this, the sequestration of CO 2 into ocean was internationally banned